PROMOTION STRATEGY THROUGH TIKTOK CONTENT DEVELOPMENT USING THE ADOBE PREMIERE PRO APPLICATION TO INCREASE BRAND AWARENESS IN MSME SILVIA SALON PUSPASARI BOGOR REGENCY - Pramudita, Audry Novia; Wardani, Tri Istining; Rochman, Fatkhur (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
The promotional strategy used by Silvia Salon Puspasari via Tiktok social media did not work optimally because the results of the uploaded videos were not optimum enough because the video quality is still not clear and unstable, which affects the upload results on Tiktok. As a result, the insight into Silvia Salon Puspasari's Tiktok account was unstable. The aim of this research was to create Tiktok content using the Adobe Premiere Pro application as promotional media. This research used the action research method. Measurement effectiveness of packaging design as promotional media using the EPIC Model method. There were 15 respondents, namely 2 marketing experts, 2 computer experts, 1 owner, and 10 consumers or potential consumers. This analysis went through 2 cycles. Based on the results of the analysis of questionnaire distribution, the first cycle still showed quite effective content. In cycle II, an EPIC Rate score of 4.6 was obtained, which means it was very effective. From this research it can be concluded that Tiktok content is said effective and suitable for use as a promotional strategy to increase brand awareness at MSME Silvia Salon Puspasari.